Revealing the chemical structure-dependent carrier trapping in one-dimensional antimony selenide photovoltaic materials. Issue 38 (6th September 2022) - Cao, Rui; Cai, Huiling; Lian, Weitao; Tang, Rongfeng; Xiang, Yinan; Wang, Yan; Chen, Tao
Abstract : Our results illustrate the absence of self-trapping in Sb2 Se3, and the maximum transient trap states are ∼10 20 cm −3 . Abstract : Carrier/exciton trapping is detrimental for photovoltaic devices. Self-trapping has been observed in antimony trisulfide (Sb2 S3 ), which has been confirmed to reduce the theoretical energy conversion efficiency in wide-band-gap Sb2 S3 (∼1.7 eV) solar cells to nearly half of the Shockley–Queisser limit. This phenomenon raises concern about the photovoltaic performance of antimony selenide (Sb2 Se3 ) in the same family, with the same crystal structure and a low band gap of 1.1–1.3 eV. However, dynamic information on their charge carriers, especially their intrinsic trapping characteristics, remains undiscovered. Herein, we conducted comparative spectral investigations into the carrier dynamics of Sb2 Se3 with both anion-rich and cation-rich characteristics. Unlike Sb2 S3, the saturation of a trapped carrier-induced absorption process indicates the limited trap states and absence of self-trapping in both the Se-rich and Sb-rich Sb2 Se3 films prepared by thermal evaporation under study. Mechanistic investigations reveal how the defect, ionicity and one-dimensional lattice distortion contribute to the carrier trapping behaviour. Furthermore, we find that Se-rich Sb2 Se3 enables the effective suppression of trap-assisted recombination and higher photovoltaic energy conversion performance in solar cells. Our study provides novel fundamental understanding regarding the ultrafast dynamic behaviour of carriers in Sb2 Se3 films and guidance for the fabrication of high-efficiency Sb2 Se3 solar cells.